Preservation of Myocardial Perfusion and Function by Keeping Hypertrophied Heart Empty and Beating for Valve Surgery: An In Vivo MR Study of Pig Hearts. (20th March 2017) - Wang, Jian; Xiang, Bo; Deng, Jixian; Lin, Hung-Yu; Freed, Darren H.; Arora, Rakesh C.; Tian, Ganghong
Abstract : Objectives . Normothermic hyperkalemic cardioplegia arrest (NHCA) may not effectively preserve hypertrophied myocardium during open-heart surgery. Normothermic normokalemic beating perfusion (NNBP), keeping hearts empty-beating, was utilized as an alternative to evaluate its cardioprotective role. Materials and Methods . Twelve hypertrophied pig hearts at 58.6 ± 7.2 days after ascending aorta banding underwent NNBP and NHCA, respectively. Near infrared myocardial perfusion imaging with indocyanine green (ICG) was conducted to assess myocardial perfusion. Left ventricular (LV) contractile function was assessed by cine MRI. TUNEL staining and western blotting for caspase-3 cleavage and cardiac troponin I (cTnI) degradation were conducted in LV tissue samples. Results . Ascending aortic diameter was reduced by 52.7 % ± 0.4 % at approximately fifty-eight days after banding. LV wall thickness was significantly higher in aorta banding than in sham operation. Myocardial blood flow reflected by maximum ICG absorbance value was markedly higher in NNBP than in NHCA. The amount of apoptotic cardiomyocyte was significantly lower in NNBP than in NHCA. NNBP alleviated caspase-3 cleavage and cTnI degradation associated with NHCA. NNBP displayed a substantially increased postoperative ejection fraction relative to NHCA. Conclusions . NNBP was better than NHCA in enhancing myocardial perfusion, inhibiting cardiomyocyte apoptosis, and preserving LV contractile function for hypertrophied hearts.